Self-Regulation of Learning and EFL Learners’ Hope and Joy: A Review of Literature - Huang, Chenhan (Frontiers in Psychology, 2022)
One of the new structures of positive psychology that has received special attention is academic self-regulation. It involves controlling one’s behavior, emotions, and thoughts to reach a long-term purpose. Learning how to self-regulate is an important skill that language learners learn both for emotional maturity and later social connections. There are various emotional factors that might be associated with the notion of self-regulation. Hope and joy are among the emotional factors that might influence language learners’ self-regulation; therefore, this literature review addresses the state of academic self-regulation in relationship with hope and joy. Reviewing the literature demonstrated that hope and joy affect language learners’ self-regulation. Hope and joy increase vitality, health, life satisfaction, and promote psychological wellbeing in EFL learners. They influence mental and physical health that is positively correlated with various scales, such as mental health, positive mood, avoidance of stressful life events, vitality and happiness in life, and problem-solving skill. The findings revealed that self-regulation in language learners depends on various demographic and educational factors that can improve learner’ language performance, mental health, and vitality of language learners. Curriculum designers and language teachers need to focus the findings of the current study on creating a more adequate and efficient language teaching environment.